High-Throughput Sequencing to Detect Novel Likely Gene-Disrupting Variants in Pathogenesis of Sporadic Brain Arteriovenous Malformations - Scimone, Concetta; Donato, Luigi; Alafaci, Concetta; Granata, Francesca; Rinaldi, Carmela; Longo, Marcello; D’Angelo, Rosalia; Sidoti, Antonina (Frontiers in Genetics, 2020)
Molecular signalling that leads to brain arteriovenous malformation (bAVM) is to date elusive and this is firstly due to the low frequency of familial cases. Conversely, sporadic bAVM is the most diffuse condition and represents the main source to characterize the genetic basis of the disease. Several studies were conducted in order to detect both germ-line and somatic mutations linked to bAVM development and, in this context, Next Generation Sequencing technologies offer a pivotal resource for the amount of outputted information. We performed Whole Exome Sequencing on a young boy affected by sporadic bAVM. Paired-end sequencing was conducted on an Illumina platform and filtered variants were validated by Sanger sequencing. We detected 20 Likely Gene-Disrupting variants affecting as many loci. Of these variants, 11 are inherited novel variants and one is a de novo nonsense variant, affecting STK4 gene. Moreover, we also considered rare known variants affecting loci involved in vascular differentiation. In order to explain their possible involvement in bAVM pathogenesis, we analysed molecular networks at Cytoscape platform. In this study we focus on some genetic point variations detected in a child affected by bAVM. Therefore, we suggest these novel affected loci as prioritized for further investigation on pathogenesis of bAVM lesions.